Explanation of challenges to health tourism development from the perspective of managers: A qualitative study - Ali Askari; Zahra Delshad; Maryam Dabirifard; Foruzan Hajiabadi; Mohsen Poursadeghiyan; Hamed Rezakhani Moghaddam; Ali Salehi Sahlabadi; Maliheh Eshaghzadeh; Robab Hosseinpour; Yusuf Hamidzadeh Arbabi (Journal of Education and Health Promotion)
Background: One way to achieve development is to expand the health tourism industry and remove its barriers. This study was conducted to explain the challenges to the development of health tourism from the perspective of managers in Ardabil province. Material and Methods: The present study is a qualitative study with a contractual content analysis approach. Participants were 18 key knowledgeable managers about tourism and health tourism. The purposeful sampling method used to select participants. Data were collected through semistructured interviews and analyzed simultaneously, and themes were explored in 2023. Results: Based on the findings of this research, seven main themes and several subcategories were investigated and identified as follows: 1) inadequate infrastructure for medical tourism; 2) ineffective governmental policies, regulations, and tariffs; 3) inadequate or subpar management practices; 4) inefficient healthcare professionals involved in health tourism; 5) lack of involvement of travel agencies in promoting health tourism; 6) absence of global information and limited involvement of local and national mass media; and 7) presence of unregulated and nonspecialized brokers. Conclusion: Managers face major obstacles to health tourism development in the province, causing economic and social damage. A better understanding of these barriers is necessary for effective planning and interventions to reduce harm and promote development.